Is the future of agriculture perennial? Imperatives and opportunities to reinvent agriculture by shifting from annual monocultures to perennial polycultures. (13th November 2018) - Crews, Timothy E.; Carton, Wim; Olsson, Lennart
Abstract : Non-technical summary: Modern agriculture is associated with numerous environmental predicaments, such as land degradation, water pollution, and greenhouse gas emission. Socio-economically, it is characterized by a treadmill of technological change, increased mechanization, and economic consolidation, while depressing economic returns to farmers. A root cause is the dominance of annual plants cultivated in monocultures. Annual crops require the yearly clearing of vegetation resulting in soil erosion and other forms of ecosystem degradation. Monocultures are susceptible to agricultural pests and weeds. By contrast, perennial polycultures informed by natural ecosystems, promise more sustainable agroecosystems with the potential to also revitalize the economic foundation of farming and hence rural societies. Abstract : Technical summary: Ten thousand years ago, humans begun domesticating wild annual plants to create the cereals and pulses that provide the mainstay of our food. The choice to domesticate annuals initiated the expansion of a novel and ecologically simple food-producing ecosystem, dependent on frequent and intense soil disturbances. Here we discuss the ecological, social and economic consequences of annual grain agriculture. In converting natural perennial ecosystems to annual crop monocultures for the provisioning of food, the ecosystems services of soil formation, nutrient retention, organic matter storage, pest suppression and others have been converted into the disservices of soil erosion, nutrient contamination, loss of organic carbon, and reliance on toxic agrochemicals. These processes are accelerated by increasing economic consolidation in agricultural industries and the relentless pursuit of economic efficiency, which has not only carried major consequences for the environment but also for the social fabric of rural societies. But a different agriculture is possible. We now have the technical capacity and ecological understanding to reinvent agriculture, so that it captures the key features of perenniality and diversity that characterize natural terrestrial ecosystems. Such a reinvention would also challenge the social and economic relations that uphold the current industrial model of agriculture.